The Evolution of the Orientalist Chronological Theory of the Quran: Methodological Shifts and Epistemological Implications for Contemporary Qur’anic Studies - Pratama, Yoga; Ilhamni, Ilhamni; Faizin, Faizin; Haliza, Nurul (An-Nida', 2025)
This study aims to examine the development of Qur’anic chronology theory as formulated by Orientalist scholars, with particular focus on Gustav Weil, William Muir, Theodor Nöldeke, and Hubert Grimme. Through a detailed analysis of the theoretical and methodological frameworks they established, this research employs a qualitative, library-based methodology, utilizing historical-critical approaches and comparative analysis to trace paradigm shifts in the construction of Qur’anic chronology. The findings reveal that the evolution of Qur’anic chronological theory occurred through several interconnected intellectual phases. Weil initiated the discourse by integrating classical Islamic narratives with Western historical methods within a historical-rational framework; Muir foregrounded biographical and theological dimensions by correlating revelation with the Prophet’s life trajectory; Nöldeke introduced a pivotal methodological transformation through his philological and linguistic approach; and Grimme emphasized dogmatic elements and theological development within the Qur’anic corpus. The progression of these theories was shaped by advancements in philology, debates concerning textual authenticity, colonial political contexts, and epistemological exchanges between Western and Muslim scholars. The study’s implications demonstrate that the construction of chronology within Orientalist discourse is neither monolithic nor static but rather continuously evolves in response to its intellectual and sociopolitical milieu. This dynamic has also fostered renewed interest in tartīb nuzūlī methodologies among contemporary Muslim scholars such as Sayyid Qutb, Bint al-Syāṭi’, and al-Jābirī, particularly in addressing the imperative for thematic and historical interpretation in Qur’anic studies.Abstrak: Penelitian ini bertujuan untuk mengeksplorasi evolusi teori kronologi Al-Qur’an yang dikembangkan oleh para orientalis, khususnya Gustav Weil, William Muir, Theodor Nöldeke, dan Hubert Grimme, melalui pembacaan atas kerangka teoretis dan metodologis yang mereka bangun. Dengan menggunakan metode kualitatif berbasis kajian pustaka, penelitian ini menerapkan pendekatan kritik-historis dan analisis komparatif untuk menelusuri perubahan paradigma dalam konstruksi kronologi Al-Qur’an. Hasil penelitian menunjukkan bahwa perkembangan teori kronologi Al-Qur’an berlangsung melalui beberapa fase intelektual yang saling berkaitan. Weil memulai dengan kerangka historis-rasional yang memadukan narasi Islam klasik dan metode sejarah Barat; Muir menekankan dimensi biografis-teologis melalui keterkaitan pewahyuan dengan perjalanan hidup Nabi; Nöldeke menghadirkan pergeseran metodologis signifikan dengan pendekatan filologis-linguistik; sedangkan Grimme menyoroti aspek dogmatis serta perkembangan teologi dalam korpus Al-Qur’an. Evolusi teori ini dipengaruhi oleh kemajuan ilmu filologi, perdebatan mengenai otentisitas teks, dinamika politik kolonial, serta interaksi epistemologis antara sarjana Barat dan Muslim. Implikasi temuan ini menunjukkan bahwa konstruksi kronologi dalam wacana orientalis tidak bersifat tunggal, melainkan terus mengalami perubahan sesuai konteks intelektual dan sosiopolitik zamannya. Dinamika tersebut turut mendorong munculnya kembali minat terhadap pendekatan tartīb nuzūlī di kalangan sarjana Muslim kontemporer, seperti Sayyid Qutb, Bint al-Syāṭi’, dan al-Jābirī, terutama dalam menjawab kebutuhan penafsiran tematik dan historis dalam studi Al-Qur’an.